Extracting limestone: How to interpret the city through ammonites and belemnites - Sadowska, Monika (Polskie Studia Krajobrazowe, 2020)
The paper analyzes the presence of the remains of ammonites and belemnites in the stones used to build the elevations of houses in modern Polish cities. The process of aestheticizing buildings is the reason for fossilized cephalopods being moved from the natural environment into urban space. I consider whether the use of such materials leads merely to making the buildings look more attractive or if this process provides an opportunity to interpret these buildings in an alternative way, which goes beyond aesthetic categories and is related to the fact that the fossils have been moved from the natural world into the cultural sphere. The limestone elements of architecture also allow one to look at the city as a unique museum of cultural and natural history.